All-pay war - Roland Hodler; Hadi Yektas (Verein für Socialpolitik, 2010)
We study a model of war in which the outcome of the war is uncertain from the perspective of the involved countries not because of luck on the battlefield (as in standard models) but because of their lack of information about their opponents. In our model there are two countries characterized by their production and military technologies and their resources. While technologies are common knowledge, resources are private information. Each country decides how to allocate its resources to production and warfare. The country with the stronger military wins and receives aggregate production. In equilibrium the country with a comparative advantage in warfare allocates its entire resources to warfare for low resource levels and follows a non-decreasing concave strategy thereafter. In response to that, the other country allocates a constant fraction of its resources to warfare for relatively low resource levels and follows an increasing non-linear strategy thereafter. Unless its military technology is much weaker than the opponent's, the country with a comparative advantage in warfare chooses the stronger military at any resource level. From an ex ante perspective it is therefore likely to win the war.
Keywords: D74; H56; D44; 330; Conflict; war; all-pay auction; private information